Emission, Fuel Consumption and Economic Analysis of Level Tunnel Proposed to Replace the Sakaltutan Pass - Demirci, Oğuz Kürşat (Fırat University, 2025)
This study quantitatively assesses the environmental and economic implications of replacing the 13 km Sakaltutan Pass on Turkey’s D-100/E-80 corridor with a proposed 11.1 km, zero-gradient tunnel. Using the This study quantitatively evaluates the environmental and economic effects of replacing the 13-km Sakaltutan Pass on the D-100/E-80 corridor with an 11.1-km, zero-gradient tunnel. Using COPERT 5.8.1 for a 5196-vehicle fleet, we apply speed, grade, cold-start and climate multipliers; assess ±15% expanded uncertainty; and run 10000-iteration Monte Carlo simulations. The tunnel scenario reduces fuel use by 5041 L day-1 (?34%) and CO2 by 12.9 t day-1 (?4700 t yr-1); NOx falls by 23%, and PM by 37%. Aggregate travel time declines by 211 h day-1, yielding ?108 million TL yr-1 in economic benefits, rising to ?126.8 million TL yr-1 when carbon valuation is included. The probability of net savings is 99.4%. Benchmarking against comparable tunnel LCAs indicates construction-phase embodied emissions on the order of 105 t CO2-eq, implying a carbon payback of ?10–20 years. Including capital expenditure, the simple payback ranges ?24–39 years, depending on CAPEX. The gains are especially pronounced for heavy-duty vehicles. Overall, the tunnel emerges as a robust option with substantial operational emission and time savings and clear long-term climate and economic value.

Bu çalışma, D-100/E-80 üzerindeki 13 km’lik Sakaltutan Geçidi yerine 11,1 km, %0 eğimli bir tünelin çevresel ve ekonomik etkilerini nicel olarak değerlendirmektedir. COPERT 5.8.1 ile 5196 araçlık filo için hız, eğim, soğuk başlatma ve iklim çarpanları kullanılmış; ±%15 genişletilmiş belirsizlik ve 10000 yinelemeli Monte Carlo analizi uygulanmıştır. Tünel senaryosu yakıt tüketimini günde 5041 L (?%34) ve CO2’yi 12,9 t gün-1 (?4700 t yıl-1) azaltır; NOx emisyonunda ?%23, PM’de ?%37 düşüş sağlar. Toplam yolculuk süresi 211 saat gün-1 azalır ve ekonomik fayda ?108 milyon TL yıl-1’dır; karbonun parasal değeri eklendiğinde toplam ?126,8 milyon TL yıl-1’a çıkar. Net tasarruf olasılığı %99,4’tür. Benzer tünel LCA’larıyla karşılaştırılan yapım aşaması gömülü emisyonları 105 t CO2-eş. mertebesindedir; karbon geri ödeme süresi ?10–20 yıl olarak öngörülür. Yatırım gideri dâhil basit geri ödeme, varsayılan yatırım gideri (CAPEX)’e bağlı olarak ?24–39 yıl aralığındadır. Sonuçlar, özellikle ağır hizmet araçları kaynaklı kazanımların belirgin olduğunu ve tünelin iklim/ekonomi açısından güçlü bir seçenek sunduğunu göstermektedir.
Sakaltutan Geçidi Yerine Önerilen Eğimsiz Tünelin Emisyon, Yakıt Tüketimi ve Ekonomik Analizi
Keywords: Internal Combustion Engines; İçten Yanmalı Motorlar; Automotive Engineering (Other); Otomotiv Mühendisliği (Diğer)